PENGARUH SUHU DALAM PROSES PENGHILANGAN KANJI POLIVINIL ALKOHOL (PVA) TERHADAP SIFAT FISIK KAIN KAPAS 100% - Kurniawan, Kurniawan; Andika Ramadhan, Haza; Oktaviani, Bintan (Politeknik STTT Bandung, 2025)
The removal of size from sarong woven fabric that has undergone yarn dyeing is very important to prepare the fabric for the next process. The handle of the sarong fabric will become stiff if the size removal process is not done perfectly. The size used to increase the strength of the yarn in the weaving of woven fabrics uses a synthetic polyvinyl alcohol size type. The size removal method is carried out using hot water by varying the process temperature of 70o C, 80o C, 90o C, and 100o C. The results of the starch removal process were evaluated for absorbency, stiffness and color difference values. The results showed that increasing the temperature of the size removal process significantly increased the effectiveness of polyvinyl alcohol removal. The optimum temperature for size removal was at 100o C, resulting in a weight reduction of 9.62%. The absorption test increased by 69.33% or 18.4 seconds. Fabric stiffness decreased drastically, with the largest decrease in stiffness of 63.15% in the warp direction and 61.3% in the weft direction. Color difference measurements showed the smallest ΔE value among other size removal temperature variations with a value of 0.36.